Economic Security of Regions - RUDENKO, Marina N. (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017DO - 10.14505//jarle.v8.8(30).29, 2018)
The urgency of the problem under investigation is caused by the need of regions (subjects of the Russian Federation) for economic security. In the conditions of the crisis, the recession in the economy, social problems in the regions of Russia are aggravated, the standard of living of the population is decreasing, and the tension in the labor market is increasing. To mitigate the negative factors affecting this, it is necessary to take decisions aimed at improving the structure of the regional economy, supporting certain industries, spheres, and attracting investments. This is all to ensure economic security. The purpose of the article is to develop recommendations of the region (subject of the federation) on the example of Perm Krai to ensure economic security. The leading methods of research of this problem are the analysis of theoretical sources, statistical analysis, comparison, SWOT-analysis. Statistical analysis occupies the most important place, since data on the economy state and social sphere of the region can be directly obtained from statistical databases. This article presents the main approaches to the concept of economic security in the region, defines the components of economic security, and compares the economic security of Perm Krai and a number of other regions. It was concluded that the economic security of Perm Krai is rather weak, which is connected with the influence of negative factors of the external environment (typical for the entire Russian economy in recent years), with unresolved problems in the region, which increase the negative influence of environmental factors. The materials of the article are of practical value for the organization of public administration at the regional level (at the level of the subject of the federation in Russia or at the level of regions in other countries), for making decisions related to ensuring the economic security of the region.